(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: To evaluate the prevalence of onychomycosis in Southern provinces of 2024. Material and method: A cross-sectional study involving 2069 individuals in five Southern provinces. Investigators collected participants’ data and performed microscopy for fungal structures in nail specimens. Data was analyzed with Microsoft Excel 365. Results: The mean age of the participants was 47,8 years (standard deviation of 11,2 years), in which females accounted for 50,9%. Most participants finished high school (46,8%) and were regularly exposed to water during their work (71,9%). Among 2069 individuals, there were 272 participants (13,1%) presenting lesions suggesting onychomycosis; from the laboratory results, there were 160/272 (58,8%) cases of fungal structure detection, including yeast (139/160, 86,9%), filamentous fungi (16/160, 10%), and combination (5/160, 3,1%). Water exposure during work was associated with onychomycosis (p = 0,01). Conclusion: Individuals with nail lesions are susceptible to fungal detection, particularly yeast. Water exposure during work may be associated with onychomycosis.